Core-modified rubyrins with phenanthrene-fused pyrrole rings: Highly selective and tunable response to Hg2+ ions. (November 2018) - Yuan, Xuemei; Li, Minzhi; Meng, Ting; Mack, John; Soy, Rodah; Nyokong, Tebello; Zhu, Weihua; Xu, Haijun; Liang, Xu
Abstract: Three fused-ring-expanded rubyrins with modified macrocyclic core have been synthesized and characterized. A series of spectroscopic, electrochemical measurements and a set of theoretical calculations demonstrate that the core-modification of the inner core of rubyrins has a large influence on the electronic structure. Colorimetric changes are observe that demonstrate that these core-modified rubyrins could be used as selective Hg 2+ ion sensors. These properties can be fine-tuned by introducing lipophilic substituents on the meso -aryl rings. Highlights: Three fused-ring-expanded rubyrins with modified macrocyclic core have been described. Core-modified rubyrins could be used as selective Hg 2+ ion sensors. Hg 2+ response could be fine-tuned by introducing meso lipophilic substituents.